Nature of Multicultural Education Curriculum - Muhammad Hifdil Islam (Kariman: Jurnal Pendidikan dan Keislaman, 2021)
Diversity is a necessity. Differences in diversity can cause problems. And one of the solutions in dealing with this is the implementation of multicultural education. The purpose of this article is to find out the essence and nature of multicultural education. The approach taken is to conduct a literature review related to multicultural education. This article discusses the curriculum and curriculum models in multicultural education. Multicultural education has the identity of personal attitudes and community groups because, with that identity, they interact and influence one another, including interactions between different cultures. Multicultural education is not a form of monocultural education, but an educational model that runs on the rails of diversity. Therefore, local identity or local culture that has diversity is a content that must exist in the multicultural education curriculum.